Design a microstrip antenna 2 elements for 900 MHz GSM system. (February 2020) - Endri, J; Ciksadan,; Setiawan, I; Handayani, A S; Taqwa, A; Husni, N F; Sitompul, C R; Amin, J M
Abstract: Microstrip antenna design aims to increase the reach of cellular devices using the GSM system because there are still areas in Indonesia that have not been reached by this service. This antenna is made with an epoxy substrate material that have a dielectric constant (εr) = 4.4 and a thickness of 1.6 mm. This antenna uses a microstrip feed channel to send information signals from radiating components to cellular devices. in this antenna design a linear array method is used which has two elements to increase the gain possessed by the antenna. in this study antenna simulation using CST Studio suite software. the results of the simulation show that the antenna has a Return loss of -59.38 dB, has a VSWR of 1.06 and have a Circular radiation pattern. Circular radiation pattern shows that the antenna can receive signals from an angle of 0 to 360 degree and can be used by mobile devices to increase the range of the GSM signal.